A membrane bioreactor for biotransformations of hydrophobic molecules using organic solvent nanofiltration (OSN) membranes - Valadez-Blanco, Rogelio (2010)
Thiswork reports the application of organic solvent nanofiltration (OSN) membranes to a membrane bioreactor for biotransformations (MBB). An organic solvent phasewas employed, allowing high substrate loadings and efficient product removal. The aqueous and organic phases were separated by an OSN membrane. The biotransformation of geraniol to R-citronellol by baker’s yeast was used as the model reaction, and n-hexadecane and toluene as the organic solvents. The performance of the MBB was compared to that of a direct contact biphasic (DCB) bioreactor. The MBB system resulted in lower productivities than the DCB system due to mass transfer limitations. For the n-hexadecane system, the membrane was the main mass transfer resistance, whereas for the toluene system the contribution of the aqueous liquid film mass transfer resistance became predominant. Further investigations are needed to improve the substrate transfer rates. Despite this, the MBB system prevented aqueous breakthrough, and thus the formation of two-phase emulsions. Toluene toxicity to the biocatalyst was also minimized, although it caused a reduction in the reaction enantiospecificity. This work showed that OSN-MBB systems avoid the formation of emulsions, thus reducing downstream separation and allowing increased substrate loadings.